2020
DOI: 10.1111/aos.14350
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of myopia in children and their parents in Hong Kong Chinese Population: the Hong Kong Children Eye Study

Abstract: To determine the myopia prevalence in Hong Kong Chinese children and their parents. Methods: It was a population-based cross-sectional study. A total of 4257 children aged 6-8 years, and 5880 parents were recruited in the Hong Kong Children Eye Study. Cycloplegic autorefraction was measured for children; and non-cycloplegic autorefraction for parents. Parental educational level, children's outdoor time, and near work were collected by validated questionnaires. Results: In children aged 6-8 years, 25.0% were my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
122
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(129 citation statements)
references
References 68 publications
5
122
1
1
Order By: Relevance
“…Tideman et al [13,14] reported that AL predicts the onset of myopia, and the correlation between refractive errors was significantly stronger with the AL/CRC ratio than with AL and CRC alone [15][16][17][18][19]. Several studies [20][21][22][23][24] reported no significant change in the AL or AL/CRC ratio before and after pupillary dilatation. erefore, the AL/CRC ratio can be a objective indicator of the onset and the progression of myopia [25].…”
Section: Discussionmentioning
confidence: 99%
“…Tideman et al [13,14] reported that AL predicts the onset of myopia, and the correlation between refractive errors was significantly stronger with the AL/CRC ratio than with AL and CRC alone [15][16][17][18][19]. Several studies [20][21][22][23][24] reported no significant change in the AL or AL/CRC ratio before and after pupillary dilatation. erefore, the AL/CRC ratio can be a objective indicator of the onset and the progression of myopia [25].…”
Section: Discussionmentioning
confidence: 99%
“…In young adults, the prevalence of myopia has reached >80% in urbanized Asian regions. A very high prevalence has been reported in South Korea (96.5% in those 19 years of age) 34 , Taiwan (86.1% in those 18-24 years of age) 35 and Hong Kong (72.2% in those <35 years of age) 16 . By contrast, a generational change exists in middle-aged and elderly adults, with a lower myopia prevalence of 19.4% in adults >65 years of age in Taiwan 36 and of 22.9% in adults in China (40-90 years of age) 37 .…”
Section: Regional Differences In Prevalencementioning
confidence: 98%
“…One of the most striking features of myopia is the high prevalence of both myopia and high myopia in some locations in East and Southeast Asia (47.0%), which is much higher than that in Central Europe (27.1%), Central Asia (17.0%) and Central Africa (7.0%) 7 . In particular, myopia prevalence is highest in urbanized areas of East and Southeast Asia such as Singapore 14 , cities in mainland China 15 , Hong Kong 16 , Taiwan 17,18 , Japan 19 and South Korea 20 . By contrast, in regions with less-intensive education systems, the prevalence of myopia is much lower (for example, Lao People's Democratic Republic, southern Indian states and Morocco) [21][22][23] .…”
Section: Regional Differences In Prevalencementioning
confidence: 99%
“…Therefore, myopia is of great concern, especially in East Asia. While the prevalence of myopia among children in some large cities in China has been reported [9][10][11][12], the prevalence of myopia among children in Chengdu has not been determined, even though Chengdu is an important central city in Western China. Children usually develop myopia at the age of 6 [13], so myopic prevention and control is needed in younger children.…”
Section: Introductionmentioning
confidence: 99%